In business - "Brown, Justin" (Hawthorn; Mimosa/McGraw-Hill, 2007)
Mike runs a pet shop, his grandfather's radio station, takes a new approach to the airport and soups up the supermarket
Donated by "Book Planet" dated: 18/4/25.
Keywords: Children's short stories, New Zealand